Social Protection and Informal Workers in Sub-Saharan Africa Lived Realities and Associational Experiences from Tanzania and Kenya - Riisgaard, Lone; Mitullah, Winnie V.; Torm, Nina (Taylor & Francis, 2022)
The promotion of social protection in Sub-Saharan Africa happens in a context where informal labour markets constitute the norm, and where most workers live uncertain livelihoods with very limited access to official social protection. The dominant social protection agenda and the associated literature come with an almost exclusive focus on donor and state programmes even if their coverage is limited to small parts of the populations - and in no way stands measure to the needs. In these circumstances, people depend on other means of protection and cushioning against risks and vulnerabilities including different forms of collective self-organizing providing alternative forms of social protection. These informal, bottom-up forms of social protection are at a nascent stage of social protection discussions and little is known about the extent or models of these informal mechanisms. This book seeks to fill this gap by focusing on three important sectors of informal work, namely: transport, construction, and micro-trade in Kenya and Tanzania. It explores how the global social protection agenda interacts with informal contexts and how it fits with the actual realities of the informal workers. Consequently, the authors examine and compare the social protection models conceptualized and implemented 'from above' by the public authorities in Tanzania and Kenya with social protection mechanisms 'from below' by the informal workers own collective associations. The book will be of interest to academics in International Development Studies, Political Economy, and African Studies, as well as development practitioners and policy communities.